(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To determine D-dimer levels before and after total hip arthroplasty and to identify factors associated with preoperative D-dimer levels. Methods: A cross-sectional study was conducted on 74 patients undergoing total hip arthroplasty at the Lower Limb Department, Ho Chi Minh city Hospital of Trauma and Orthopedics, from September 2017 to September 2018. Blood samples were collected for D-dimer testing at 24 hours before surgery and at 24, 48, and 72 hours postoperatively. D-dimer concentrations were measured using the automated coagulation analyzer Sta-Rmax. Results: The mean D-dimer level at 24 hours preoperatively was 1.40 ± 1.44 µg/mL. Postoperative levels were 2.20 ± 1.44 µg/mL at 24 hours, 1.50 ± 0.79 µg/mL at 48 hours, and 1.77 ± 0.81 µg/mL at 72 hours. Preoperative D-dimer levels were significantly associated with age group, occupation, body mass index, alcohol consumption, hypertension, preoperative immobilization, and the cause of hip disease. Patients aged ≥ 60 years had a higher proportion of D-dimer > 0.5 µg/mL than those < 60 years (p = 0.003). Patients with hypertension had higher D-dimer levels > 0.5 µg/mL than those without hypertension (p = 0.004). Preoperative immobilized patients had higher D-dimer levels than non-immobilized patients (p = 0.01). Patients undergoing total hip arthroplasty due to trauma had higher preoperative D-dimer levels than those with degenerative hip disease (p = 0.003). Conclusion: Most patients undergoing total hip arthroplasty had elevated D-dimer levels (> 0.5 µg/mL) both before and after surgery. Therefore, D-dimer testing should be used to screen for venous thromboembolism in order to enable early diagnosis and timely prevention in patients undergoing total hip arthroplasty.